Diversidad de palmas en la amazonía peruana con énfasis en la selva baja (Loreto, Ucayali, Madre de Dios) del Perú - Grandez Rios, Cesar Augusto (2021)
At the beginning of this century, 2003, a team of researchers from the University of Aarhus headed by Dr. Henrik Balslev carried out scientific expeditions in order to study Palms in the Peruvian Amazon, taking over the three Amazon regions, in order to investigate the diversity of palms. In the Amazon, a total of 354 transects of 5 X 100 m were made, making a general total of 88.50 hectares, inventoried in the three regions, in the Loreto region for being the most extensive, 239 transects were made, with 254,018 individuals. Ucayali 38 transects with 70,777 individuals and Madre de Dios 77 transects and 28,392 individuals. In total, 353,034 individuals are being reported for the 3 regions, Loreto registers the greatest diversity, being Oenocarpus batua "hungurahui" the most abundant with 28,898 individuals representing 10 percent of the individuals, in Ucayali Lepidocaryum tenue "irapay" with 14,379 individuals representing 20% of total individuals and for Madre de Dios is Geonoma deversa “palmiche” with 5,743 individuals with 20 percent of total individuals. According to the Shanon Loreto index it is the most diverse with 3,601, Ucayali with 3,061 and Madre de Dios with 2,839 respectively. Regarding the similarity in the two Regions, Loreto and Ucayali there is a 73 percent similarity, between Ucayali and Madre de Dios there is a 47 percent similarity and between Loreto and Madre de Dios there is a 35 percent similarity.